Study of Efficiency Level Road Rigid Pavement and Flexible Pavement - Febria, Tara; Trikomara, Rian; Taufik, Hendra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This study is to analyze the operational costs, maintenance on Rigid Pavement (RF) and Flexible Favement (FP). Project design life is 20 years. Design Method at Simpang Beringin Maredan Siak for RP is PdT-14-2003, while FP is use PtT PL-01-2002-B method of Highways. The primary data was gained from survey the average daily car movement (LHR) documentation and secondary data which was collected from the details of the work’s volume, unit price list, unit price analysis, heavy equipment leasing, and maintenance costs during the design life of 20 years. As a result, RP thickness by using the method of Highways produced concrete pavement thickness of 27 cm, 10cm layer of concrete foundation, reinforcement dowel Ø 33 mm plain and reinforcement tie D166 mm threaded bar and FP produced layer of asphalt concrete pavement thickness of (AC-WC) 4,2cm, layer of asphalt concrete (AC-BC) 6 cm, class A aggregate based layer was 25 cm, class B aggregate based layer was 50 cm. RP cost of Rp. 17,232,129,032.15 and FP cost of Rp.13,780,354,350.72. the difference betwwen two cost is around 20.03%. The costs for maintenance bending pavement was Rp. 56,809,224,912.16 and rigid pavement maintenance costs Rp.44,033,259,315.85 the different of both of charge of approximately 22.49% in terms of pavement with a design life of 20 years.Keywords: Rigid Pavement, Flexible Pavement, Unit Price, Budget Plan, Simpang Maredan.